2020
DOI: 10.22430/24223182.1616
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family–Work and Work–Family Conflict on Call Center Workers’ Emotional Exhaustion With Person–Job Fit as Antecedent

Abstract: In accordance with the government’s regulations in Indonesia, all financial services institutions are obliged to implement a customer complaint handling mechanism, which has contributed to the rapid growth of the call center industry. As a benchmark for managing service quality, call center workers are required to always keep their emotions stable despite the continuous pressures and unpleasant responses from customers. For this reason, working at call centers is now considered a job with a high emotional burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
2
6
0
3
Order By: Relevance
“…Furthermore, the study also explained that affective commitment moderates the relationship between WPLC and burnout, but partially has a significant effect only on the dimension of cynicism. In line with research conducted by Dwi Lestari & Yuwono (2020) which discusses conflicts in employees and person job fit. The results revealed that person job fit was negatively associated with family work and work-family conflict, and emotional exhaustion.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the study also explained that affective commitment moderates the relationship between WPLC and burnout, but partially has a significant effect only on the dimension of cynicism. In line with research conducted by Dwi Lestari & Yuwono (2020) which discusses conflicts in employees and person job fit. The results revealed that person job fit was negatively associated with family work and work-family conflict, and emotional exhaustion.…”
Section: Resultssupporting
confidence: 70%
“…The entire study is a quantitative description study and uses sampling techniques of nonprobabability sampling. The measuring instrument used in all studies used the Maslach Burnout Inventory (MBI) questionnaire (Geraldes et al, 2019;Gonçalves et al, 2020;Dwi Lestari & Yuwono, 2020;Montalbo, 2016;Drissi et al, 2021;Charoensukmongkol & Puyod, 2020;Harry, 2021;Deniz & Kaya, 2021). Kuesione is distributed in person as well as online.…”
Section: Methodsmentioning
confidence: 99%
“…The Braunstein-Bercovitz et al (2012) research revealed that the relationship between personality variables (e.g., resilience) and well-being was partially mediated by WFC and FWC. Lestari (2020) reported that PJ fit had a negative impact on both WFC and FWC. In addition, FWC mediated the relationship between PJ fit and emotional exhaustion.…”
Section: Psychological Capital Person-job Fit Conflicts In the Work-f...mentioning
confidence: 99%
“…Tourism activities in Indonesia have recently begun to grow, develop, and even become a trend and lifestyle in Indonesian society (Sunjayadi, 2018;Chen & Ting, 2019). As a result, tourism activities are expected to become a mainstay sector able to drive other closely related economic sectors (Mishra et al, 2011;Cheah & Abdul-Rahim, 2018;Dwi Lestari & Yuwono, 2020). The Indonesian government, following its development program in the next five years, will focus on the land and maritime infrastructure, energy, food, and tourism sectors.…”
Section: Introductionmentioning
confidence: 99%